Kontribusi Ekranisasi Sastra Dalam Penulisan Resensi Bagi Siswa Sma Di Karanganyar Jawa Tengah - Ali Imron Al-Ma’ruf; Gallant Karunia Assiddik (Prosiding University Research Colloquium, 2022)
In recent decades, the extenuation of literature or the conversion of literature into film is a mass media that is very popular with the public, especially students. On the other hand, literature learning in Indonesia, on average, has yet to be a lesson that students are interested in. Many students feel dislike literature lessons. Through literature, students can learn in many ways, including character education and film review writing. Therefore, examining the contribution of utilizing literary exclusion in developing film review writing through academic learning is necessary. The purpose of this study is to describe the following: (1) The contribution of exploring Indonesian literature as a medium for developing film/cinema review writing among high school students, (2) The response of the student community to the contribution of literary ekranization as a medium for learning literature in schools, (3) Implementing academic learning with literary ekranization media in developing film review writing for high school students. This research uses the qualitative descriptive method. A qualitative approach is used to obtain data in greater depth and describe phenomena in the field objectively. The data of this study is in the form of qualitative data, namely data in the form of words, sentences, and discourses or images in films resulting from literary excranization. Data sources include the film Saat Cinta Bertasbih, resource persons, Indonesian teachers and students, and documents. Data were collected through observation techniques by watching the film Saat Cinta Bertasbih, in-depth interviews with students and teachers, and document analysis. Data analysis is carried out by the semiotic model reading method, including heuristic and hermeneutic readings. The results showed: (1) The ekranization of Indonesian literature has a significant contribution to academic learning in order to develop student's skills in writing film reviews; (2) The enthusiasm of the high school student community towards the explanatory literature as a medium for learning literature in schools is very evident, it is evident that all students are fully involved in watching the film When Love Is Celebrated; (3) Learning by utilizing the literary excranization of the novel Saat Cinta Bertasbih as a medium in the development of film review writing is carried out through seven steps. In summary, students were asked to sit back and watch a screening of the film When Love Is Prayed, and then the students wrote a film review. The majority of students can write a good When Love Is Good